A palatalização do /s/ pós-vocálico: uma análise variacionista da transferência fonológica do falar paraibano (L1) na aquisição de inglês (L2) - Lima, Priscila Evangelista Morais e (2014)
Several researches have been conducted with the aim of analyzing the phenomenon of the palatalization in Brasilian Portuguese (PB), of which we can highlight the Carvalho (2000), Brescancini (2002) Callou, Leite & Moraes (2002), Hora (2003), Silva (2004), Macedo (2004), Brandão (2008), Monteiro (2009), among others. However studies on the palatalization of coronal fricative in the acquisition of English as L2 are rather scarce. That said this study aims to identify the palatalization in the production of /S/ post-vocalic in the context /S/t realized by paraibanos speakers of English as L2. Specifically, we propose to identify the process of the palatalization in the interlanguage (IL) of English learners as L2, what are the factors which favor or not the application of the rule, and if there are no linguistics agents promoting palatalization. This study is based on Sociolinguistics Variationist formulated by Labov (2008 [1972]) and the theoretical basis of the Acquisition of L2 (SELINKER, 1992; ELLIS, 2003 [1994]; BAYLE, 2007). The Sociolinguistics and Acquisition of L2 interface has emerged as a new field of linguistic studies. In order to study the relationship between social context and the learning of a L2, the union of these two fields wants to explain how extralinguistic factors may interfere in using a new code. Some studies (BAYLEY, 2005; LUCENA & ALVES, 2009; CAGLIARI, 2010; LIMA, 2012) have been realized in this perspective. The corpus of this research is consisted by 18 paraibanos informants belonging to the basic, intermediate, and advanced levels. To collect speech data it was recorded the reading of eighteen sentences and two texts in English. The collected material was quantitatively analysed through the computer program GOLDVARB X (SANKOFF; TAGLIAMONTE; SMITH, 2005). The independent variables observed were level of proficiency, explicit phonological awareness, tonicity, preceding phonological context, and type of instrument. The statistical analysis performed showed, in increasing order of significance, that the variables level of proficiency in language, tonicity and preceding context were those more relevant to the implementation of palatalization.